A Prospective Multicenter Registry on Feasibility, Safety, and Outcome of Endovascular Recanalization in Childhood Stroke (Save ChildS Pro) - Sporns, Peter B.; Kemmling, André; Lee, Sarah; Fullerton, Heather; Kunz, Wolfgang G.; Wilson, Jenny L.; Mackay, Mark T.; Steinlin, Maja; Fiehler, Jens; Psychogios, Marios; Wildgruber, Moritz (Frontiers in Neurology, 2021)
Rationale Early evidence for the benefit of mechanical thrombectomy (MT) in pediatric patients with intracranial large vessel occlusion has been shown in previous retrospective cohorts. Higher level evidence is needed to overcome the limitations of these studies such as the lack of a control-group and the retrospective design. Randomized trials will very likely not be feasible and several open questions remain, for example the impact of arteriopathic etiologies or a possible lower age limit for MT. Save ChildS Pro therefore aims to demonstrate the safety and effectiveness of MT in pediatric patients compared to best medical management and intravenous thrombolysis. Design Save ChildS Pro is designed as a worldwide multicenter prospective registry comparing the safety and effectiveness of mechanical thrombectomy to best medical care alone in the treatment of pediatric arterial ischemic stroke. It will include pediatric patients (<18 years) with symptomatic acute intracranial arterial occlusion who underwent either MT or best medical treatment including intravenous thrombolysis. Outcomes The primary endpoint of Save ChildS Pro is the modified Rankin Scale score (mRS) at 90-day poststroke. Secondary endpoints will comprise the decrease of the Pediatric National Institutes of Health Stroke Scale (PedNIHSS) score from admission to discharge and rate of complications. Discussion Save ChildS Pro aims to provide high level evidence for MT for pediatric patients with arterial ischemic stroke, thereby improving functional outcome and quality of life and reducing the individual, societal, and economic burden of death and disability resulting from pediatric stroke. Save ChildS Pro is registered at the German Clinical Trials Registry (DRKS; Identifier DRKS00018960).